Utilization of Telemedicine Services for Mental Health Care in Malaysia During the COVID-19 Pandemic: A Cross-Sectional Study - Jati bin Deris (Journal of Community Health Provision, 2023)
There has been an increase in the use of telemedicine services due to the COVID-19 pandemic's severe impact on the delivery of mental health care. The purpose of this research was to analyze how mental health services were delivered via telemedicine in Malaysia during the 2009 COVID-19 epidemic. In order to better understand the experiences of adults who have used telemedicine for mental health treatment, a cross-sectional survey was carried out. The data was analyzed using descriptive statistics and logistic regression. Most people who used telemedicine for mental health care were content with the experience, suggesting that the services were widely adopted. The likelihood of using telemedicine services for mental health care increased considerably with younger age, higher education level, and the presence of preexisting mental health conditions. However, people have mentioned concerns about privacy, lack of personal contact with healthcare providers, and technical difficulties as reasons for not using telemedicine. These results show the promise of telemedicine services for mental health treatment in Malaysia and the necessity of maintaining efforts to remove obstacles to their use. Telemedicine services for mental health care in Malaysia and other nations need more study to determine their long-term efficacy and viability.